2015
DOI: 10.1007/s00590-015-1703-5
|View full text |Cite
|
Sign up to set email alerts
|

Revision hip arthroplasty using impacted cancellous bone and cement: a long-term follow-up study

Abstract: Acetabular bone deficiency is one of the many challenging problems encountered in revision hip arthroplasty. A variety of surgical options and techniques are available including impaction bone grafting. We present our long-term experience of 68 consecutive cups in 64 patients, using impacted cancellous bone grafting with bone cement. With a mean follow-up of 10.5 year (IQR 7.5-12.9) after revision surgery, three implants had undergone further revision. Three patients had subsequent femoral peri-prosthetic frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…The functional outcome scores all improved significantly after surgery and patients reported a high satisfaction rate in accordance with earlier literature (Arumugam et al. 2015 , Te Stroet et al. 2015b ).…”
Section: Discussionsupporting
confidence: 91%
“…The functional outcome scores all improved significantly after surgery and patients reported a high satisfaction rate in accordance with earlier literature (Arumugam et al. 2015 , Te Stroet et al. 2015b ).…”
Section: Discussionsupporting
confidence: 91%
“…In this series, the success rate of bone graft impaction was excellent [19 out of 20 patients; 95%], following at least 2 years of follow up. Arumugam et al [13] studied sequential 64 cup revision with follow-up period of 10 years, with survival rate of the graft being 95.5%. Verspeek et al [14] reported higher failure rate [27%; 13 out of 44] in their 15 years follow-up study.…”
Section: Discussionmentioning
confidence: 99%
“…11 IBG is a well-established surgical technique pioneered by the Nijmegen 12 and Exeter 13 Group; a technique that can restore deficient acetabular bone stock and recreate anatomic center of rotation with a standard size acetabular socket even in Paprosky 3 and AAOS type III defects with favorable survivorships. 9,10,[14][15][16] Due to aseptic loosening, the survivorship of acetabular components in IBG ranged from 100% at 10 years 17 to 85% after 20 years and 77% after 25 years. 18 Only by restoring bone stock, future revisions and re-revisions can be undertaken with ease.…”
Section: Introductionmentioning
confidence: 99%